The performance of tele-cervicography for detection of preinvasive and invasive disease of the uterine cervix as an adjunctive test to Pap smears - Kyehyun Nam; Soo-Nyung Kim; Seung-hyuk Sim; Seijun Han (Contemporary Oncology)
Aim of the study To evaluate the diagnostic capacity of tele-cervicography for the detection of cervical neoplasia as an adjunctive test with Papanicolaou (Pap) smears. Material and methods : Pap smear and tele-cervicography were performed on each subject. Histologic results were obtained for all patients. Results : Of the 863 females who had a tele-cervigram, 252 (29.2%) had a positive result. Of the 60 histologically confirmed cases of high-grade squamous intraepithelial lesions (HSILs), 56 (93.3%) were detected by tele-cervicography, including 16 (26.7%) with a positive grade of 1 and 40 (66.7%) with a positive grade of 2. With the positive threshold of tele-cervicography set as any positive grade (P0 to P3), the overall sensitivity was 94.0% (95% CI: 88.0–97.3%), the specificity was 80.9% (95% CI: 80.0–81.5%), and the positive likelihood ratio was 4.94 (95% CI: 4.23–5.77) for the detection of HSILs or cancer. The combination of tele-cervicography with Pap smear testing for the detection of HSILs or cancer resulted in an increase in sensitivity from 84.6% (Pap only: cutoff = atypical squamous cells of undetermined significance or more severe) to 98.3% (Pap plus tele-cervicography: cutoff = P0 or more severe). Conclusions : The sensitivity of tele-cervicography was higher than that of cytology for the detection of cervical neoplasia, and combining the two tests increased the sensitivity. Tele-cervicography can be considered a useful complementary tool to cytology.